Core business regulation and dual diversification patterns in the telecommunications industry - Kashlak, Roger; Joshi, Maheshkumar P. (Strategic Management Journal, 1994)
Abstract A firm is confronted with the separate decisions of product and international diversification. It is suggested that these postures are linked to external contingencies in firms who face core business regulation. A technique is developed to explain dual diversification patterns using evidence obtained from the new industry comprised of the Regional Bell Operating Companies (RBOCs).